2009
DOI: 10.3201/eid1501.080815
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia helveticainDermacentor reticulatusTicks

Abstract: We report on the molecular evidence that Dermacentor reticulatus ticks in Croatia are infected with Rickettsia helvetica (10%) or Rickettsia slovaca (2%) or co-infected with both species (1%). These fi ndings expand the knowledge of the geographic distribution of R. helvetica and D. reticulatus ticks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 13 publications
3
42
0
1
Order By: Relevance
“…autumn and spring), in which period this tick species is usually sampled for the detection of rickettsiae (e.g. Dobec et al, 2009). Thus, relevant prevalence rates from single-habitat sampling should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…autumn and spring), in which period this tick species is usually sampled for the detection of rickettsiae (e.g. Dobec et al, 2009). Thus, relevant prevalence rates from single-habitat sampling should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of the authors' knowledge, most (if not all) of these studies are based on the molecular analysis of ticks collected in a limited part of the questing period (e.g. Dobec et al, 2009;Reye et al, 2013), not taking into account potential seasonal variations in the rate of infection with tick-borne rickettsiae, or not mentioning seasonal data at all (Wójcik-Fatla et al, 2013). The objective of this study was to provide an example, in which it is shown that for a more accurate determination of the prevalence rates of D. reticulatus-borne rickettsiae it is inevitable to include samples from the whole tick season.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9). These bacteria have been found in Dermacentor marginatus and Dermacentor reticulatus ticks in a great majority of European countries, with a high percentage of ticks infected with these bacteria (208,(280)(281)(282)(283)(284)(285)(286)(287)(288)(289)(290). Dermacentor ticks usually bite hairy domestic and wild animals (291).…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 99%
“…It has been generally accepted that I. ricinus is the main vector of R. helvetica. However, D. reticulatus ticks were found to be infected with R. helvetica in Croatia (Dobec et al, 2009). Serosurveys have found antibodies reactive to R. helvetica in 1.9%-12.5% of the population and PCR positive cases were confirmed in France (Davoust et al, 2012), Italy (Corrain et al, 2012, Austria (Sonnleitner et al, 2012), Poland (Chmielewski et al, 2011) andSweden (Nilsson et al, 2010).…”
Section: Rickettsia Helveticamentioning
confidence: 99%